PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD MELALUI TEKNIK HANDS ON MATHEMATICS BERBANTUAN LKS TERHADAP PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH - Teni Suriani; Yulia Rahmawati Z (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
This study aims to describe students' mathematical abilities assisted by LKS with the STAD type cooperative learning model through the Hand On Mathematical technique. Researchers used a quantitative approach in the form of Quasi Experiment. The study population was class VIII SMP N 43 Padang and the samples of this study were students of class VIII.1 as the experimental group who received treatment with the STAD type cooperative learning model through hand on mathematics techniques and VIII.2 as the control class who received conventional learning. The research instrument is in the form of a final test to see the understanding of mathematical concepts and problem solving. The results of the analysis show that: 1) The understanding of mathematical concepts taught by the STAD-type cooperative learning model through the hand on mathematics technique with LKS-assisted is better than that taught by conventional learning, 2) The mathematical problem-solving ability taught by the STAD-type cooperative learning model through the STAD-type cooperative learning technique. Hand on mathematics assisted by LKS is better than what is taught with conventional learning in class VIII SMP N 43 Padang.